Category Shifts in Paulo Coelho’s The Winner Stands Alone Novel in Indonesian Translation - Kanimolia Kedoh; June A Jacob; Ifoni Ludji (Pusat Kegiatan Belajar Masyarakat (PKBM) Sambi Poleng, 2023)
This paper aims to discover the types of category shifts used in The Winner Stands Alone's Indonesian translation and the dominant type of category shifts used in The Winner Stands Alone's Indonesian translation. The data were taken from Paulo Coelho's English novel The Winner Stands Alone and its Indonesian translation, Sang Pemenang Berdiri Sendirian. This writing belongs to Qualitative research. The type of data used in this research is documentary. The data analysis shows that all category shifts, namely structure, class, unit, and intra-system shifts, occurred in The Winner Stands Alone novel's Indonesian translation. There were 293 cases of category shifts that occurred. Structure shift with 135 data or 46,07% out of 293 total data, followed by unit shift with 96 data or 32,77% out of 293 total data, the intra-system shift with 37 data or 12,63% out of 293 total data, and the class shift with 25 data or 8,53% out of 293 total data. Therefore, structure shift is the dominant type of category shift that occurred in the Indonesian translation of The Winner Stands Alone novel